Strategi Kegiatan Pendidikan Di Sekolah Relevan Dengan Perkembangan Dan Perubahan Zaman - Taufiq Harris; Etiyasningsih Etiyasningsih (Universitas Islam Lamongan, 2023)
This study is aimed to describe education in schools so that it is relevant to the dynamics of the times. This study uses qualitative methods using library research. The results of this study indicate that schools are able to effectively follow the changes in the times by implementing strategies in the form of programs, namely; (1) continuous teacher training, especially on teaching management systems, 2) schools have consultants for teachers, (3) teaching activity models in the form of actions (4) schools have good cooperative relationships with student parents, communities, and institutions, (5) schools develop innovation.